Behavioural Monitoring Underlines Habituation to Repeated Stressor Stimuli in Farmed Gilthead Sea Bream (Sparus aurata) Reared at a High Stocking Density - Paul G. Holhorea; Fernando Naya-Català; Ricardo Domingo-Bretón; Federico Moroni; Álvaro Belenguer; Josep À. Calduch-Giner; Jaume Pérez-Sánchez (Biology)
A confinement stress test with 75% tank space reduction and behavioural monitoring through tri-axial accelerometers externally attached to the operculum was designed. This procedure was validated by demonstrating the less pronounced stress response in gilthead sea bream than in European sea bass (950–1200 g). Our study aimed to assess habituation to high stocking densities with such procedure in gilthead sea bream. Animals (420–450 g) were reared (June–August) in a flow-through system at two stocking densities (CTRL: 10–15 kg/m3; HD: 18–24 kg/m3), with natural photoperiod and temperature (21–29 °C), and oxygen levels at 5.2–4.2 (CTRL) and 4.2–3.2 ppm (HD). At the end, blood and muscle were sampled for haematology and transcriptomic analyses, and external tissue damage was assessed by image-based scoring. Four days later, fish underwent a 45 min confinement stress test over two consecutive days. HD fish showed reduced feed intake, growth rates and haematopoietic activity. Muscle transcriptome changes indicated a shift from systemic to local growth regulation and a primed muscle regeneration over protein accretion in HD animals with slight external injuries. After stress testing, HD fish exhibited a decreased recovery time in activity and respiration rates, which was shorter after a second stressor exposure, confirming habituation to high densities.